Assessment of the ichthyofauna in stretches under the influence of Salto Grande Reservoir (Middle Paranapanema River, SP/PR, Brazil). - Brandao, H.; Vidotto-Magnoni, A.P.; Ramos, I.P.; Carvalho, Edmir Daniel [UNESP] (My University, 2009)
Aim: To analyze the composition, species richness and spatial distribution of the fish fauna in the area under influence of the Salto Grande Reservoir; Methods: Fish were caught every two months from November/05 to October/06, using gill nets, seining nets and sieve; Results: It was registered 67 fish species, 1,964 individuals and 146.2 kg, representing CPUEn of 1,964 and CPUEb of 278 kg. The most representative orders were Characiformes, with 29 species, Siluriformes (21 species) and Perciformes (11 species) Nine non-native species were registered. The most abundant species in the reservoir were Astyanax altiparanae, Steindachnerina insculpta and Acestrorhynchus lacustris, indicating the predominance of medium and small fishes in this reservoir. The dendrogram of similarity separated the Dam and Pedra Branca stretches from Pardo River Mouth, indicating differences in the assemblages. The species turnover among the stretches was demonstrated by the beta diversity, which may be related to the diversity of habitat; Conclusions: Although being a small reservoir, it displays great habitat diversity, reflecting in the composition and structure of fish assemblages.

Objetivo: analisar a composição, a riqueza e a distribuição espacial da fauna de peixes dos diversos trechos sob a área de influência do reservatório de Salto Grande; Métodos: Foram realizadas coletas bimestrais no período de novembro/05 a outubro/06, utilizando-se de redes de espera, arrasto e peneirão; Resultados: Foram registradas 67 espécies, 1.964 indivíduos e 146,2 kg, representando CPUEn de 3.804 indivíduos e CPUEb de 278 kg. As ordens mais representativas foram Characiformes, com 29 espécies, Siluriformes (21 espécies) e Perciformes (11 espécies). Cabe ressaltar que nove espécies são não-nativas. As espécies mais abundantes no reservatório como um todo foram Astyanax altiparanae, Steindachnerina insculpta e Acestrorhyncus lacustris, indicando o predomínio de peixes de médio e pequeno porte neste reservatório. O dendograma de similaridade distanciou os trechos Barragem e Pedra Branca do trecho Foz do rio Pardo, indicando diferenças nas assembleias. A análise da diversidade mostrou que ocorre substituição de espécies entre os trechos o que pode estar relacionado com a diversidade de habitats; Conclusões: Embora o reservatório seja pequeno, apresenta grande diversidade de habitats, o que reflete na composição e estrutura das assembléias de peixes.
Levantamento da ictiofauna nos trechos sob influência do reservatório de Salto Grande (Médio Rio Paranapanema, SP/PR, Brasil)